Uptake of DU145 and LNCaP prostate cancer cell line derived extracellular vesicles is inversely correlated with blood–brain barrier integrity in vitro - Ana Špilak; Adrián Klepe; Sophia Theresa Kriwanek; Heinz-Peter Friedl; Andreas Brachner; Christa Nöhammer; Winfried Neuhaus (Fluids and Barriers of the CNS)
Abstract Background Tumor-derived small extracellular vesicles (sEVs) have been implicated in changes of the blood–brain barrier (BBB) during pre-metastatic niche formation. Although it was postulated that sEVs can traverse the highly restrictive BBB via transcytosis—data mostly based on the indirect detection of transported cargo—direct evidence for sEV transport across the BBB remains elusive due to challenges in sEV labelling, detection limits, and inherent limitations of existing in vitro BBB models. This study investigated the interaction and effects of sEVs derived from low (LNCaP) and moderately metastatic (DU145) prostate cancer (PCa) cell lines with the human brain endothelial cell line hCMEC/D3. Methods Systematic optimization of the cell culture membrane insert set-up for sEV transport studies was accomplished with inserts with different pore sizes, varied coating procedures and medium compositions. Particle size distribution, quantification and zeta-potential was measured with nanoparticle tracking analysis. Uptake of fluorescent labelled sEVs by hCMEC/D3 cell layers was determined by flow cytometry, barrier integrity was measured by transendothelial electrical resistance (TEER). Effects of inflammatory cytokines and PCa lines-derived sEVs on hCMEC/D3 at the transcriptomic level were investigated by means of high-throughput qPCR based on Fluidigm Biomark® platform. Results Improved conditions for sEV transport studies included the application of membrane inserts with 1 µm pore size and of 1% BSA in the receiver compartment. Efficiency of LNCaP- and DU145-derived sEV uptake by hCMEC/D3 cells revealed an inverse correlation between uptake of sEVs and paracellular barrier integrity (TEER). Whereas addition of sEVs of the more aggressive DU145 cells resulted in a distinct increase of TEER under regular and inflammatory conditions, LNCaP-derived sEVs affected TEER only upon inflammatory cytokine treatment. MRNA expression analyses of hCMEC/D3 cells revealed a distinct regulation of transcripts depending on TEER (i.a. FN, CDLN1) or upon inflammatory cytokines (i.a.: ABCB1, MFSD2a, VCAM1, VEGFa). Conclusions Differences upon treatment of hCMEC/D3 layers with LNCaP-and DU145 derived sEVs indicated that vesicles retain and transport molecular features of their originating cells. Careful optimization of the test set-up for studies with sEVs in vitro is recommended, including medium controls for sEV purification and labelling as well as addition of proteins for sEV recovery.